Comparative electron microscopy analysis of internal limiting membrane and epiretinal membrane ultrastructure from vitrectomy surgery: A study protocol - Thananop Pothikamjorn; Thanapong Somkijrungroj; Marisa Prasanpanich; Nuntachai Surawatsatien; Wasee Tulvatana (PLoS ONE, 2025)
The epiretinal membrane (ERM) is a fibrocellular layer that forms on the inner surface of the retina, often leading to visual impairment and significantly impacting visual function. Understanding the pathophysiology of ERM formation is crucial for advancing ophthalmic care and improving patient outcomes. This research aims to investigate the pathophysiology of ERM by comparing the internal limiting membrane (ILM) pathology in patients with and without ERM. The study involves a comprehensive protocol of ILM and ERM specimens collection during pars plana vitrectomy and membrane peeling procedures. Specimens are assessed using both light microscopy and transmission electron microscopy to evaluate morphological and ultrastructural changes. The study employs a standardized protocol for specimen collection and analysis, focusing on identifying differences in cell counts, extracellular matrix components, and ultrastructural alterations in the ILM. We also investigate the correlation between pathological findings and clinical biomarkers, including fundus photography, optical coherence tomography (OCT), optical coherence tomography angiography (OCT-A), and baseline characteristics such as patient demographics and underlying diseases. These clinical assessments provide a comprehensive understanding of the ocular environment and its relationship to ERM formation. By examining both the ILM and ERM in patients with and without ERM, the study aims to identify distinct pathological features associated with ERM development. We also aimed to elucidate whether changes in the ILM, such as cellular proliferation and extracellular matrix remodeling, are significant contributors to ERM formation. Additionally, the study will explores how these pathological changes correlate with clinical features and biomarkers, offering insights into potential mechanisms driving ERM pathogenesis. Establishing these correlations would support the hypothesis that ILM changes contribute to ERM development, while the absence of significant differences may suggest alternative pathways. Ultimately, this research aims to enhance our understanding of ERM pathophysiology, paving the way for improved prognosis and therapeutic strategies.